Sulfonated-cellulose as catalysts for the efficient conversion of levulinic acid into ethyl levulinate - Reynoso, Rodrigo Agustín (2024)
The present study highlighted the use of cellulose sulfuric acid (CSA) as heterogeneous catalyst, reusable, preparation easy and derivate of biomass (Cortaderia Selloana), for the synthesis of ethyl levulinate by catalytic esterification of levulinic acid (LA) with ethanol. The effects of temperature, catalyst loading and relation molar EtOH:LA on the yield to ethyl levulinate (EL) were studied in order to optimize its production. A yield of 95 % was obtained at 16 h, 80 °C and molar relation ethanol:LA (3:1). These results demonstrate that is possible obtained good yields to EL using derivate biomass catalyst.